ANALYZING COHESION IN STUDENTS’ RECOUNTS TEXT: A DISCOURSE-BASED INVESTIGATION - Purnama, Dody Wahyudi (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This study aimed to investigate the use of grammatical cohesive devices in the recount writing of 10th-grade students at SMAN 1 Puasakanagara Subang Subang. Employing a qualitative descriptive method, the analysis focused on six recount texts to identify the frequency of references, conjunctions, ellipses, and substitution. The results revealed that conjunctions were the most frequently used cohesive technique, with counts of 20, 13, 16, 17, 19, and 20. Ellipses appeared less frequently, with counts of 8, 9, 10, 8, and 9, while substitution was absent in all texts. References were the dominant device, showing counts of 30, 23, 18, 20, 25, and 23, with the highest percentage of 52% in text 1. These findings indicate that students effectively utilized references and conjunctions, enhancing the coherence of their writing. The limited use of ellipses and the absence of substitution suggest a preference for clarity in academic contexts. The study recommends that students focus on the logical and consistent application of cohesive devices to further improve the quality of their writing.